An Analysis of Code Mixing Used by Maudy Ayunda on Her Youtube Channel - Fahlefi, Indra; Novitri, Novitri; Harfal, Zaldi (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2024)
This study aimed to identify and analyze the types and functions of code mixing used by Maudy Ayunda on Her YouTube Channel. Using a qualitative descriptive research design, it consist of 15 videos from Maudy’s YouTube channel. Data was collected through observation and documentation techniques, and analyzed using Hoffmann’s (1991) theory to determine the types of code mixing, and Hoffmann (1991), Saville-Troike (1986), and Holmes (2013) theories to identify the functions of code mixing. The findings showed that most frequently used types of code mixing was intra-sentential code mixing. Followed by Intra-lexical code mixing and Involving a change of pronounciation was not found in the videos. The function of emphasis was the most common function found in the videos, followed by Lexical Needs, Quoting Somebody Else, Repitition Use for Clarificayion, Talking about Particualr Topic, and Being Emphatic about Something. There are three functions which is not found on Muady’s videos are interjection, Expressing Group Identity or Solidarity, and Clarifying the Speech for the Interluctor. These findings suggest the importance of considering sociolinguistic factors in language education.